Implementation And Standards Of National Education Management: How To Implement Education In Indonesia - Elsa Yulianingsih (Jurnal Mantik, 2021)
Education is essentially a conscious and planned effort to create a learning atmosphere and learning process so that students are actively able to develop the various potentials that exist in themselves, education also has a very strategic role in advancing the nation and state, for that it is necessary to have an education management ideal and well-organized. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that, through the Government Regulation (PP) of the Republic of Indonesia Number 19 of 2005 concerning National Education Standards (SNP) mandates that every education unit at the primary and secondary education levels must prepare curriculum by referring to Content Standards, Graduate Competency Standards, Education Management Standards, Process Standards, and Assessment Standards, as well as guided by the guidelines prepared by the National Education Standards Agency. Education management standards are standards in managing education in an educational institution, in essence the management of education is an integral component and cannot be separated from the education process as a whole.